Caveats to Governing With Empathy. (3rd September 2022) - Fenley, Vanessa M.
Abstract: In recent years, scholars have called for integrating empathy into the practice and scholarship of public administration. As a concept gaining traction in the field, greater conceptual clarity is needed. This paper contributes to efforts to develop the concept of empathy for public administration by highlighting potential misapplications, thus encouraging the field to recognize empathy's negative as well as positive aspects. Specifically, it addresses concerns related to misdirecting empathy to the wrong target (filtered empathy), misattributing the source of the other's emotions (false empathy), and overlooking broader social structures and power dynamics shaping interactions. Examining these caveats highlights opportunities to be more intentional with empathy's use in citizen-state relations, in marketing practices in public and nonprofit organizations, and in developing the skills and knowledge of public administrators.